Translation in Qualitative Social Research: The Possible Impossible - Wolff-Michael Roth (Forum: Qualitative Social Research, 2013)
In an increasingly globalized world of research, communicating with scholars in the same language and culture and with scholars from other cultures and linguistic background is a sine qua non in/of all sciences, including those using qualitative social research. The nature of language is at least latently recognized especially by those scholars who communicate with their peers in a non-native language, such as English, which has become de facto the scientific lingua franca. Although many are aware of the difficulties of rendering something a scholar wants to say in another language, the nature of language as a non-self-identical process is hardly if ever articulated. Instead, the metaphysical idea of the same "meanings" that can be rendered in multiple languages by means of translation—literally, "carried across"—is endemic to the scientific culture. In the very definition of science (e.g., in the description of research methods), experiments must operate the same (must be reproducible) wherever and by whomever these are conducted. In this contribution to the debate concerning translation, conducted in the context of the FQS debate "Quality of Qualitative Research," I articulate theoretical and pragmatic dimensions on the topic, drawing on empirical investigations, literary works, and philosophical investigations to explicate how translation is both theoretically impossible and pervasively achieved in/as everyday praxis.